High-performance refractory ceramic composite pipe and method for manufacturing the same

CN122916693APending Publication Date: 2026-10-16YANGZHOU HENGXIN SPECIAL STEEL PIPE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611158982.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]为了克服现有技术中耐火陶瓷复合管存在的晶粒异常长大、烧结致密度不足、界面结合强度较低以及抗热震性能和抗渣侵蚀性能有待提高问题,本发明的目的在于提供一种高性能耐火陶瓷复合管及其制备方法

Benefits of technology

[0024]This invention employs aluminum dihydrogen phosphate and zirconium oxychloride to synergistically modify alumina powder. Aluminum dihydrogen phosphate forms a stable aluminophosphate bond structure on the surface of alumina particles, while zirconium oxychloride forms a zirconium-based reinforcing structure. Their synergistic effect constructs a uniform and stable interfacial transition layer on the alumina particle surface, not only improving the interfacial bonding strength between particles but also promoting particle rearrangement and mass migration during sintering, thus facilitating a denser sintered microstructure. Simultaneously, this invention introduces 5-sulfosalicylic acid as a grain boundary regulating component. Its unique functional group structure enhances the dispersion uniformity of each component and promotes grain boundary homogenization during sintering, inhibiting abnormal grain growth and thereby improving the consistency and stability of the material's internal microstructure. Through the synergistic effect of aluminum dihydrogen phosphate-zirconia oxychloride modified alumina powder and 5-sulfosalicylic acid, combined with a multiphase reinforcement system constructed from mullite powder, zirconium oxide, silicon carbide micro powder and magnesium oxide, the resulting refractory ceramic composite pipe possesses excellent sintering density, flexural strength, fracture toughness, wear resistance, thermal shock resistance and slag erosion resistance. It can meet the requirements for long-term stable use in high temperature, high wear and complex corrosion environments, and significantly extend the service life of refractory ceramic composite pipe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916693A_ABST
    Figure CN122916693A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high-performance refractory ceramic composite pipe and preparation method thereof, belong to refractory ceramic material technical field.High-performance refractory ceramic composite pipe includes aluminium dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder, mullite powder, zirconia, silicon carbide micro powder, 5-sulfosalicylic acid, magnesium oxide, silicon powder, borate sintering aid, binder and dispersant;Aluminium dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder is obtained by the synergistic modification of aluminium dihydrogen phosphate and zirconium oxychloride to alumina powder.The interface structure of aluminium dihydrogen phosphate-zirconium oxychloride synergistic modification is constructed in the application, and the crystal boundary organization is regulated by 5-sulfosalicylic acid, the sintering density and interface bonding strength of material are improved, abnormal grain growth is inhibited, and the organization structure is promoted uniformization.Refractory ceramic composite pipe has excellent flexural strength, thermal shock stability, wear resistance and slag resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of refractory ceramic materials technology, specifically relating to a high-performance refractory ceramic composite pipe and its preparation method. Background Technology

[0002] Refractory ceramic composite pipes are functional materials that combine high temperature resistance, wear resistance, corrosion resistance, and high strength. They are widely used in metallurgy, power, building materials, chemical, mining, and solid waste treatment industries, and are particularly suitable for conveying high-temperature particulate matter, slurry, slag, and corrosive media. As industrial equipment develops towards higher temperatures, larger sizes, and longer operating cycles, higher requirements are placed on the mechanical properties, thermal shock stability, and service life of refractory ceramic composite pipes.

[0003] Currently, ceramic materials such as alumina, mullite, and zirconium oxide are widely used in the preparation of refractory ceramic composite pipes due to their excellent refractory and wear-resistant properties. Alumina possesses high hardness and wear resistance, mullite has a low coefficient of thermal expansion and good thermal stability, and zirconium oxide has a certain toughening effect. However, existing refractory ceramic composite pipes are still prone to problems such as abnormal grain growth, high porosity, and weak interfacial bonding during high-temperature sintering, which limits the material's flexural strength, thermal shock resistance, and slag erosion resistance. Under long-term high-temperature and alternating hot and cold environments, microcracks are easily generated inside the material and gradually propagate, thus shortening its service life.

[0004] To address the aforementioned issues, existing technologies typically employ methods such as adding sintering aids, toughening phases, or surface modification of ceramic powders to improve material properties. However, traditional single-modification methods often struggle to simultaneously address multiple requirements, including sintering densification, grain boundary strengthening, and improved thermal stability. Furthermore, some modified systems are prone to failure during high-temperature sintering, resulting in limited reinforcement effects. Therefore, developing a high-performance refractory ceramic composite pipe with high interfacial bonding strength, uniform microstructure, excellent high-temperature resistance, and good thermal shock stability, along with its preparation method, is of great significance for improving the overall performance and service life of refractory ceramic composite pipes. Summary of the Invention

[0005] To overcome the problems of abnormal grain growth, insufficient sintering density, low interfacial bonding strength, and the need to improve thermal shock resistance and slag erosion resistance in existing refractory ceramic composite pipes, this invention aims to provide a high-performance refractory ceramic composite pipe and its preparation method. This invention uses aluminum dihydrogen phosphate-zirconia oxychloride synergistically modified alumina powder as a reinforcing phase. The alumina powder is synergistically modified by aluminum dihydrogen phosphate and zirconium oxychloride, and combined with 5-sulfosalicylic acid, mullite powder, zirconium oxide, silicon carbide micropowder, magnesium oxide, silica micropowder, and borate sintering aids to construct a multiphase synergistic reinforcement system. The high-performance refractory ceramic composite pipe is obtained through mixing, ball milling, granulation, molding, and high-temperature sintering. The high-performance refractory ceramic composite pipe obtained by this invention has a uniform microstructure, strong interfacial bonding, high sintering density, high flexural strength, excellent wear resistance, good thermal shock resistance, and strong slag erosion resistance.

[0006] The objective of this invention can be achieved through the following technical solutions:

[0007] A high-performance refractory ceramic composite pipe comprises the following raw materials in parts by weight: 80-140 parts of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder; 20-60 parts of mullite powder; 5-20 parts of zirconium oxide; 3-15 parts of silicon carbide micro powder; 0.5-8 parts of 5-sulfosalicylic acid; 1-10 parts of magnesium oxide; 2-15 parts of silica micro powder; 0.5-6 parts of borate sintering aid; 1-8 parts of binder; and 0.1-3 parts of dispersant. The aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder is prepared by synergistic modification of alumina powder with aluminum dihydrogen phosphate and zirconium oxychloride.

[0008] Optionally, the aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder comprises the following raw materials in parts by weight: 80-150 parts alumina powder; 3-20 parts aluminum dihydrogen phosphate; 2-15 parts zirconium oxychloride; 30-120 parts ethanol; and 40-150 parts deionized water.

[0009] Optionally, the preparation method of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder includes the following steps:

[0010] (1) Add aluminum dihydrogen phosphate to a mixed solvent of ethanol and deionized water and stir to dissolve. Then add zirconium oxychloride and continue stirring to obtain aluminum dihydrogen phosphate-zirconium oxychloride precursor solution.

[0011] (2) Add aluminum oxide powder to the aluminum dihydrogen phosphate-zirconium oxychloride precursor solution for dispersion treatment to obtain a mixture, so that aluminum dihydrogen phosphate and zirconium oxychloride are uniformly loaded on the surface of aluminum oxide powder;

[0012] (3) The mixture was aged, then filtered, washed and dried to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder.

[0013] Optionally, the reaction conditions in step (1) are as follows: aluminum dihydrogen phosphate is added to a mixed solvent consisting of ethanol and deionized water, and stirred at 400-600 rpm for 0.5-2 h at 50-65 °C, followed by the addition of zirconium oxychloride and continued stirring for 1-3 h.

[0014] Optionally, the reaction conditions in step (2) are to disperse the mixture at 500-800 rpm for 1-4 hours at 55-75°C.

[0015] Optionally, the aging conditions in step (3) are aging at 40-70°C for 6-18 hours; the drying conditions in step (3) are drying at 90-110°C for 8-18 hours.

[0016] Optionally, the borate sintering aid is composed of boric acid and sodium tetraborate in a mass ratio of (1-5):(1-3); the binder is composed of silica sol and aluminum dihydrogen phosphate in a mass ratio of (2-8):(1-4); and the dispersant is composed of ammonium polyacrylate and sodium hexametaphosphate in a mass ratio of (1-5):(1-3).

[0017] Optionally, a method for preparing a high-performance refractory ceramic composite pipe includes the following steps:

[0018] S1. Weigh out aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder, mullite powder, zirconium oxide, silicon carbide micro powder, 5-sulfosalicylic acid, magnesium oxide, silica micro powder and borate sintering aid according to the weight parts, and mix them evenly to obtain composite powder.

[0019] S2, Add binder and dispersant to composite powder, mix evenly and then ball mill to obtain mixed slurry, and then dry and granulate the mixed slurry to obtain composite ceramic particles;

[0020] S3, the composite ceramic particles are pressed into a tubular blank, which is then dried and sintered, and after cooling, a high-performance refractory ceramic composite pipe is obtained.

[0021] Optionally, the ball milling conditions in S2 are a ball milling time of 4 to 12 hours and a ball-to-material ratio of (1 to 5):1; the drying and granulation temperature is 80 to 150°C.

[0022] Optionally, the molding pressure in S3 is 50–200 MPa; the drying temperature is 90–150°C, and the drying time is 6–24 h; the sintering temperature is 1450–1700°C, and the sintering time is 2–10 h.

[0023] The beneficial effects of this invention are:

[0024] This invention employs aluminum dihydrogen phosphate and zirconium oxychloride to synergistically modify alumina powder. Aluminum dihydrogen phosphate forms a stable aluminophosphate bond structure on the surface of alumina particles, while zirconium oxychloride forms a zirconium-based reinforcing structure. Their synergistic effect constructs a uniform and stable interfacial transition layer on the alumina particle surface, not only improving the interfacial bonding strength between particles but also promoting particle rearrangement and mass migration during sintering, thus facilitating a denser sintered microstructure. Simultaneously, this invention introduces 5-sulfosalicylic acid as a grain boundary regulating component. Its unique functional group structure enhances the dispersion uniformity of each component and promotes grain boundary homogenization during sintering, inhibiting abnormal grain growth and thereby improving the consistency and stability of the material's internal microstructure. Through the synergistic effect of aluminum dihydrogen phosphate-zirconia oxychloride modified alumina powder and 5-sulfosalicylic acid, combined with a multiphase reinforcement system constructed from mullite powder, zirconium oxide, silicon carbide micro powder and magnesium oxide, the resulting refractory ceramic composite pipe possesses excellent sintering density, flexural strength, fracture toughness, wear resistance, thermal shock resistance and slag erosion resistance. It can meet the requirements for long-term stable use in high temperature, high wear and complex corrosion environments, and significantly extend the service life of refractory ceramic composite pipe. Attached Figure Description

[0025] The invention will now be further described with reference to the accompanying drawings.

[0026] Figure 1 The image shows a comparison of the infrared spectra of alumina powder and alumina powder synergistically modified with aluminum dihydrogen phosphate and zirconium oxychloride. Detailed Implementation

[0027] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.

[0028] Example 1: The purpose of this example is to verify the feasibility of preparing high-performance refractory ceramic composite pipes using the lower limit ratio of each component and under lower reaction conditions.

[0029] S1. Add 3 parts of aluminum dihydrogen phosphate to a mixed solvent consisting of 30 parts of ethanol and 40 parts of deionized water, and stir at 400 rpm for 0.5 h at 50 °C to ensure complete dissolution. Then add 2 parts of zirconium oxychloride and continue stirring for 1 h to obtain an aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. Then add 80 parts of alumina powder and stir at 500 rpm for 1 h at 55 °C to obtain a mixture. Aging the obtained mixture at 40 °C for 6 h, filtering, washing, and drying at 90 °C for 8 h yields aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder.

[0030] S2. Weigh 80 parts of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder, 20 parts of mullite powder, 5 parts of zirconium oxide, 3 parts of silicon carbide micro powder, 0.5 parts of 5-sulfosalicylic acid, 1 part of magnesium oxide, 2 parts of silica micro powder and 0.5 parts of borate sintering aid and mix evenly. Then add 1 part of binder and 0.1 part of dispersant, mix evenly and then ball mill for 4 hours at a ball-to-material ratio of 1:1 to obtain a mixed slurry. Then dry and granulate at 80℃ to obtain composite ceramic particles.

[0031] S3. The composite ceramic particles are pressed into a tubular blank at a molding pressure of 50 MPa, then dried at 90°C for 6 hours, sintered at 1450°C for 2 hours, and naturally cooled to room temperature to obtain a high-performance refractory ceramic composite tube.

[0032] Example 2: The purpose of this example is to verify the effect of the aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder and 5-sulfosalicylic acid synergistic reinforcement system on the comprehensive performance improvement of refractory ceramic composite pipes when the components are in the median ratio and under moderate reaction conditions.

[0033] S1. 11.5 parts of aluminum dihydrogen phosphate were added to a mixed solvent consisting of 75 parts of ethanol and 95 parts of deionized water. The mixture was stirred at 500 rpm for 1 h at 58 °C to ensure complete dissolution. Then, 8.5 parts of zirconium oxychloride were added and the reaction was continued for 2 h to obtain an aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. Then, 115 parts of alumina powder were added and dispersed at 650 rpm for 2.5 h at 65 °C to obtain a mixture. The resulting mixture was aged at 55 °C for 12 h, filtered, washed, and dried at 100 °C for 12 h to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder. Figure 1 It can be seen that the unmodified alumina powder is mainly located at 3440 cm⁻¹. -1 An OH stretching vibration peak appears nearby, at 1630 cm⁻¹. -1 The characteristic peak of adsorbed water appeared nearby, and at 520 cm⁻¹ -1 and 460cm -1 An Al-O framework vibrational peak appeared nearby; after synergistic modification with aluminum dihydrogen phosphate and zirconium oxychloride, a peak was observed at 3440 cm⁻¹. -1 The weakening of the hydroxyl absorption peak near the surface indicates that the modified component interacts with the hydroxyl groups on the alumina surface; at 1250 cm⁻¹ -1 1140cm -1 and 1050cm -1 New characteristic absorption peaks appear nearby, corresponding to the P-OH, PO-Al, and POP vibration peaks, respectively; at 950 cm⁻¹ -1 and 585cm -1The presence of Zr-OP and Zr-O characteristic peaks nearby indicates that zirconium oxychloride successfully participated in the construction of the interface structure. The above results show that aluminum dihydrogen phosphate and zirconium oxychloride have been successfully loaded on the alumina surface and formed a stable Al-OP-Zr synergistic modification structure.

[0034] S2. Weigh 110 parts of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder, 40 parts of mullite powder, 12.5 parts of zirconium oxide, 9 parts of silicon carbide micro powder, 4.25 parts of 5-sulfosalicylic acid, 5.5 parts of magnesium oxide, 8.5 parts of silica micro powder, and 3.25 parts of borate sintering aid, mix them evenly, then add 4.5 parts of binder and 1.55 parts of dispersant, mix evenly, and then ball mill for 8 hours at a ball-to-material ratio of 3:1 to obtain a mixed slurry; then dry and granulate at 115℃ to obtain composite ceramic particles;

[0035] S3. The composite ceramic particles are pressed into a tubular blank at a molding pressure of 120 MPa, then dried at 120°C for 12 hours, and then sintered at 1575°C for 6 hours. After natural cooling to room temperature, a high-performance refractory ceramic composite tube is obtained.

[0036] Example 3: The purpose of this example is to verify the performance of high-performance refractory ceramic composite pipes prepared under the upper limit ratio of each component and under high reaction conditions.

[0037] S1. 20 parts of aluminum dihydrogen phosphate were added to a mixed solvent consisting of 120 parts of ethanol and 150 parts of deionized water. The mixture was stirred at 600 rpm for 2 hours at 65°C to ensure complete dissolution. Then, 15 parts of zirconium oxychloride were added and the reaction was continued for 3 hours to obtain an aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. Then, 150 parts of alumina powder were added and dispersed by stirring at 800 rpm for 4 hours at 75°C to obtain a mixture. The resulting mixture was aged at 70°C for 18 hours, filtered, washed, and dried at 110°C for 18 hours to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder.

[0038] S2. Weigh 140 parts of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder, 60 parts of mullite powder, 20 parts of zirconium oxide, 15 parts of silicon carbide micro powder, 8 parts of 5-sulfosalicylic acid, 10 parts of magnesium oxide, 15 parts of silica micro powder, and 6 parts of borate sintering aid, mix them evenly, then add 8 parts of binder and 3 parts of dispersant, mix evenly, and then ball mill for 12 hours at a ball-to-material ratio of 5:1 to obtain a mixed slurry; then dry and granulate at 150℃ to obtain composite ceramic particles;

[0039] S3. The composite ceramic particles are pressed into a tubular blank at a molding pressure of 200 MPa, then dried at 150°C for 24 hours, sintered at 1700°C for 10 hours, and naturally cooled to room temperature to obtain a high-performance refractory ceramic composite tube.

[0040] Comparative Example 1: The purpose of this comparative example is to verify the effect of using only aluminum dihydrogen phosphate to modify alumina powder without introducing zirconium oxychloride for synergistic modification on the performance of refractory ceramic composite pipes.

[0041] S1. Add 11.5 parts of aluminum dihydrogen phosphate to a mixed solvent consisting of 75 parts of ethanol and 95 parts of deionized water, and stir at 500 rpm for 1 h at 58 °C to ensure complete dissolution; then add 115 parts of alumina powder, and stir at 650 rpm for 2.5 h at 65 °C to obtain a mixture; age the obtained mixture at 55 °C for 12 h, filter, wash, and dry at 100 °C for 12 h to obtain aluminum dihydrogen phosphate-modified alumina powder;

[0042] S2. Weigh 110 parts of aluminum dihydrogen phosphate-modified alumina powder, 40 parts of mullite powder, 12.5 parts of zirconium oxide, 9 parts of silicon carbide micro powder, 4.25 parts of 5-sulfosalicylic acid, 5.5 parts of magnesium oxide, 8.5 parts of silica micro powder, and 3.25 parts of borate sintering aid, mix them evenly, then add 4.5 parts of binder and 1.55 parts of dispersant, mix evenly, and then ball mill for 8 hours at a ball-to-material ratio of 3:1 to obtain a mixed slurry; then dry and granulate at 115℃ to obtain composite ceramic particles.

[0043] S3. The composite ceramic particles are pressed into a tubular blank at a molding pressure of 120 MPa, then dried at 120°C for 12 hours, and then sintered at 1575°C for 6 hours. After natural cooling to room temperature, a refractory ceramic composite tube is obtained.

[0044] Comparative Example 2: The purpose of this comparative example is to verify the effect of using only zirconium oxychloride to modify alumina powder without introducing aluminum dihydrogen phosphate for synergistic modification on the performance of refractory ceramic composite pipes.

[0045] S1. Add 8.5 parts of zirconium oxychloride to a mixed solvent consisting of 75 parts of ethanol and 95 parts of deionized water, and stir at 500 rpm for 2 hours at 58°C to ensure full dispersion; then add 115 parts of alumina powder, and stir at 650 rpm for 2.5 hours at 65°C to obtain a mixture; age the obtained mixture at 55°C for 12 hours, filter, wash, and dry at 100°C for 12 hours to obtain zirconium oxychloride-modified alumina powder;

[0046] S2. Weigh 110 parts of zirconium oxychloride-modified alumina powder, 40 parts of mullite powder, 12.5 parts of zirconium oxide, 9 parts of silicon carbide micro powder, 4.25 parts of 5-sulfosalicylic acid, 5.5 parts of magnesium oxide, 8.5 parts of silica micro powder, and 3.25 parts of borate sintering aid, mix them evenly, then add 4.5 parts of binder and 1.55 parts of dispersant, mix evenly, and then ball mill for 8 hours at a ball-to-material ratio of 3:1 to obtain a mixed slurry; then dry and granulate at 115℃ to obtain composite ceramic particles.

[0047] S3. The composite ceramic particles are pressed into a tubular blank at a molding pressure of 120 MPa, then dried at 120°C for 12 hours, and then sintered at 1575°C for 6 hours. After natural cooling to room temperature, a refractory ceramic composite tube is obtained.

[0048] Comparative Example 3: The purpose of this comparative example is to verify the effect of not adding 5-sulfosalicylic acid organic small molecules on the performance of refractory ceramic composite pipes.

[0049] S1. 11.5 parts of aluminum dihydrogen phosphate were added to a mixed solvent consisting of 75 parts of ethanol and 95 parts of deionized water. The mixture was stirred at 500 rpm for 1 h at 58 °C to ensure complete dissolution. Then, 8.5 parts of zirconium oxychloride were added and the reaction was continued for 2 h to obtain an aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. Then, 115 parts of alumina powder were added and dispersed at 650 rpm for 2.5 h at 65 °C to obtain a mixture. The resulting mixture was aged at 55 °C for 12 h, filtered, washed, and dried at 100 °C for 12 h to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder.

[0050] S2. Weigh 110 parts of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder, 40 parts of mullite powder, 12.5 parts of zirconium oxide, 9 parts of silicon carbide micro powder, 5.5 parts of magnesium oxide, 8.5 parts of silica micro powder, and 3.25 parts of borate sintering aid, mix them evenly, then add 4.5 parts of binder and 1.55 parts of dispersant, mix evenly, and then ball mill for 8 hours at a ball-to-material ratio of 3:1 to obtain a mixed slurry; then dry and granulate at 115℃ to obtain composite ceramic particles;

[0051] S3. The composite ceramic particles are pressed into a tubular blank at a molding pressure of 120 MPa, then dried at 120°C for 12 hours, and then sintered at 1575°C for 6 hours. After natural cooling to room temperature, a refractory ceramic composite tube is obtained.

[0052] Performance testing:

[0053] 1. Flexural strength test

[0054] The high-performance refractory ceramic composite tubes prepared in the examples and comparative examples were processed into test specimens with dimensions of 120mm × 25mm × 25mm. After drying at 110℃ for 24 hours, a three-point bending test was performed using an electronic universal testing machine. The span was set to 100mm, and the loading rate was set to 0.5mm / min. The maximum load at which the specimen fractured was recorded, and the flexural strength was calculated. Each group of specimens was tested in parallel five times, and the average value was taken as the final test result.

[0055] 2. Thermal shock stability test

[0056] The high-performance refractory ceramic composite tube samples prepared in the examples and comparative examples were placed in a 1000℃ high-temperature furnace and held for 30 min. Then, they were quickly removed and immersed in 25℃ water for 10 min to complete one thermal shock cycle. The thermal shock cycle test was repeated, and the number of thermal shock cycles corresponding to the appearance of obvious cracks on the sample surface or the decrease in flexural strength retention rate to below 80% of the initial value was recorded to evaluate the thermal shock stability of the material.

[0057] 3. Wear resistance test

[0058] The high-performance refractory ceramic composite tubes prepared in the examples and comparative examples were processed into standard samples, and their wear performance was tested using a high-temperature wear testing machine. Under a load of 50N and a rotation speed of 300r / min, alumina sand was used as the abrasive for continuous wear for 60min. The mass of the sample was weighed before and after the test, and the wear amount per unit area was calculated. Each group of samples was tested in parallel three times, and the average value was taken as the final test result, with the unit being mg / cm².

[0059] 4. Slag erosion resistance test

[0060] The high-performance refractory ceramic composite tubes prepared in the examples and comparative examples were processed into standard samples. Cylindrical grooves of uniform specifications were drilled into the surface of the samples and filled with an equal mass of simulated blast furnace slag. The samples were then placed in a 1500℃ high-temperature furnace and held for 3 hours. After cooling, the samples were cut along the center of the groove, and the slag erosion depth was measured using a metallographic microscope. The erosion depth was used to characterize the material's resistance to slag erosion. Each group of samples was tested in triplicate, and the average value was taken as the final test result.

[0061] Table 1. Performance test results of the examples and comparative examples.

[0062] Example 1 108.6 36 18.4 2.12 Example 2 136.8 52 11.3 1.28 Example 3 124.7 45 14.1 1.63 Comparative Example 1 92.5 29 24.6 3.05 Comparative Example 2 95.8 31 22.8 2.87 Comparative Example 3 101.2 34 20.3 2.36

[0063] As shown in Table 1, the refractory ceramic composite pipes prepared in different embodiments and comparative examples exhibit significant differences in flexural strength, thermal shock stability, wear resistance, and slag erosion resistance. Among them, Example 2 showed the best performance in all performance indicators, indicating that under the median ratio and moderate reaction conditions, a more reasonable synergistic reinforcement system can be formed among the components, which is beneficial to fully utilizing the comprehensive reinforcing effect of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder and 5-sulfosalicylic acid.

[0064] Regarding flexural strength, Example 2 achieved a flexural strength of 136.8 MPa, significantly higher than Examples 1, 3, and the comparative examples. Analysis suggests that the synergistic modification with aluminum dihydrogen phosphate and zirconium oxychloride forms a stable interfacial reinforcement structure on the alumina particle surface, improving interparticle bonding strength. Furthermore, 5-sulfosalicylic acid further promotes grain boundary homogenization and inhibits abnormal grain growth, resulting in a denser microstructure. In contrast, Comparative Examples 1 and 2 used only a single modification method, resulting in insufficient interfacial reinforcement and thus significantly reduced flexural strength.

[0065] Regarding thermal shock stability, Example 2 maintained good structural integrity after 52 thermal shock cycles, outperforming Examples 1, 3, and the comparative examples. This is because the synergistic modification system improves the internal structural uniformity of the material, reduces local stress concentration, and the zirconia toughening phase and mullite stabilizing phase effectively inhibit crack initiation and propagation under thermal stress, thereby improving the material's resistance to alternating thermal shocks. Comparative Examples 1 and 2, lacking the synergistic modification effect, showed a significant reduction in the number of thermal shock cycles.

[0066] Regarding wear resistance, Example 2 exhibited the lowest wear amount at only 11.3 mg / cm², indicating it possessed the best wear resistance. Analysis suggests that the synergistic modification of alumina powder and silicon carbide micropowder formed a more stable hard framework structure, while sintering resulted in higher density, reducing particle shedding during wear and thus significantly decreasing wear. In contrast, the relatively loose microstructure formed by the single modification system led to a significant increase in wear in Comparative Examples 1 and 2.

[0067] Regarding slag erosion resistance, the slag erosion depth of Example 2 was only 1.28 mm, significantly lower than other samples. This indicates that the synergistic modification system can effectively improve the internal pore structure of the material, increase grain boundary bonding strength, and reduce the possibility of high-temperature slag penetrating along pores and grain boundaries. Simultaneously, the optimization effect of 5-sulfosalicylic acid on the grain boundary structure further enhances the material's erosion resistance. Although Comparative Example 3 used synergistically modified alumina powder, its slag erosion resistance was still lower than that of Example 2 due to the lack of grain boundary regulation effect from 5-sulfosalicylic acid.

[0068] In summary, this invention, by constructing a synergistic modification system of aluminum dihydrogen phosphate-zirconium oxychloride alumina powder and 5-sulfosalicylic acid, can significantly improve the flexural strength, thermal shock stability, wear resistance, and slag erosion resistance of refractory ceramic composite pipes. Example 2, in particular, achieved optimal performance in all indicators, fully demonstrating the excellent comprehensive performance and promising application prospects of this invention.

Claims

1. A high-performance refractory ceramic composite pipe, characterized in that, The raw materials include the following parts by weight: 80-140 parts of aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder; 20-60 parts of mullite powder; 5-20 parts of zirconium oxide; 3-15 parts of silicon carbide micro powder; 0.5-8 parts of 5-sulfosalicylic acid; 1-10 parts of magnesium oxide; 2-15 parts of silica micro powder; 0.5-6 parts of borate sintering aid; 1-8 parts of binder; and 0.1-3 parts of dispersant. The aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder is prepared by synergistic modification of alumina powder with aluminum dihydrogen phosphate and zirconium oxychloride.

2. The high-performance refractory ceramic composite pipe according to claim 1, characterized in that, The aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder comprises the following raw materials in parts by weight: 80-150 parts alumina powder; 3-20 parts aluminum dihydrogen phosphate; 2-15 parts zirconium oxychloride; 30-120 parts ethanol; and 40-150 parts deionized water.

3. A high-performance refractory ceramic composite pipe according to claim 1 or 2, characterized in that, The preparation method of the aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder includes the following steps: (1) Add aluminum dihydrogen phosphate to a mixed solvent of ethanol and deionized water and stir to dissolve. Then add zirconium oxychloride and continue stirring to obtain aluminum dihydrogen phosphate-zirconium oxychloride precursor solution. (2) Add aluminum oxide powder to the aluminum dihydrogen phosphate-zirconium oxychloride precursor solution for dispersion treatment to obtain a mixture, so that aluminum dihydrogen phosphate and zirconium oxychloride are uniformly loaded on the surface of aluminum oxide powder; (3) The mixture was aged, then filtered, washed and dried to obtain aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder.

4. The high-performance refractory ceramic composite pipe according to claim 3, characterized in that, The reaction conditions for step (1) are as follows: aluminum dihydrogen phosphate is added to a mixed solvent consisting of ethanol and deionized water, and stirred at 400-600 rpm for 0.5-2 h at 50-65 °C, followed by the addition of zirconium oxychloride and continued stirring for 1-3 h.

5. A high-performance refractory ceramic composite pipe according to claim 3, characterized in that, The reaction conditions for step (2) are to stir and disperse at 500-800 rpm for 1-4 hours at 55-75℃.

6. The high-performance refractory ceramic composite pipe according to claim 3, characterized in that, The aging conditions for step (3) are aging at 40-70℃ for 6-18 hours; the drying conditions for step (3) are drying at 90-110℃ for 8-18 hours.

7. A high-performance refractory ceramic composite pipe according to claim 1, characterized in that, The borate sintering aid is composed of boric acid and sodium tetraborate in a mass ratio of (1-5):(1-3); the binder is composed of silica sol and aluminum dihydrogen phosphate in a mass ratio of (2-8):(1-4); and the dispersant is composed of ammonium polyacrylate and sodium hexametaphosphate in a mass ratio of (1-5):(1-3).

8. A method for preparing a high-performance refractory ceramic composite pipe, characterized in that, The preparation method includes the following steps: S1. Weigh out aluminum dihydrogen phosphate-zirconium oxychloride synergistic modified alumina powder, mullite powder, zirconium oxide, silicon carbide micro powder, 5-sulfosalicylic acid, magnesium oxide, silica micro powder and borate sintering aid according to the weight parts, and mix them evenly to obtain composite powder. S2, Add binder and dispersant to composite powder, mix evenly and then ball mill to obtain mixed slurry, and then dry and granulate the mixed slurry to obtain composite ceramic particles; S3, the composite ceramic particles are pressed into a tubular blank, which is then dried and sintered, and after cooling, a high-performance refractory ceramic composite pipe is obtained.

9. The method for preparing a high-performance refractory ceramic composite pipe according to claim 8, characterized in that, The ball milling conditions in S2 are: ball milling time of 4 to 12 hours and ball-to-material ratio of (1 to 5):1; the drying and granulation temperature is 80 to 150°C.

10. The method for preparing a high-performance refractory ceramic composite pipe according to claim 8, characterized in that, The molding pressure in S3 is 50-200 MPa; the drying temperature is 90-150℃ and the drying time is 6-24 h; the sintering temperature is 1450-1700℃ and the sintering time is 2-10 h.